Artificial Intelligence as an Object of Global Digital Governance - Levchenko, Diana; Левченко, Діана Сергіївна; Левченко, Діана (Науково-дослідний інститут публічного права, 2024)
The article offers the author’s understanding of the essence of artificial intelligence as a phenomenon of the digital society. The features of artificial intelligence as conditions for the transformation of global digital governance are determined. The relevance of the adoption of the Global Digital greement within the framework of the UN as a normative step in the creation of a worldwide system of principles and mechanisms for the transparent and accountable use of artificial intelligence is highlighted. The ethical challenges of introducing artificial intelligence into global digital governance are evealed. Attention is focused on ensuring access to digital technologies and resources (including artificial intelligence) for developing countries as a direction for the development of global digital governance. It is summarized that artificial intelligence is the driving force of changes in global governance. The important role of international cooperation in the development of uniform standards, ethical principles and inclusive models of management, which should become the basis for a harmonious combination of technical progress with humanitarian values, is determined.
Keywords: governance; space; space activities; development; artificial intelligence; global administration; global cooperation